THEORETICAL FOUNDATIONS AND GEORGIAN PRACTICE OF GREEN FINANCING FOR SUSTAINABLE DEVELOPMENT - Merab Vanishvili; Irakli Katsadze (International Journal of Innovative Technologies in Social Science, 2025)
The research focuses on the challenges and prospects for developing green finance, which provides funds for achieving the UN Sustainable Development Goals. The objectives of the study are to assess the level of development and structure of green finance, as well as to identify the factors determining its development, taking into account recent trends in the global economy.The article analyzes the state and development trends of the green finance market, identifies barriers to the development of green financial instruments, proposes solutions to emerging problems, and identifies the specific features of sustainable finance development In Georgia.The study utilized the concept of sustainable development and a problem-oriented approach to green finance. The analytical work was conducted using methods of analysis and synthesis, comparison and grouping, economic analysis, and modeling.The study results showed that interest in green finance instruments is driven by societal demands for sustainable development and environmental conservation, which require stricter accountability requirements for green financial instruments, more stringent regulatory oversight, and reliable disclosure of information supported by more accurate data.Conclusions were drawn regarding the need to stimulate the use of green financing instruments and develop a legal framework for sustainable development that will ensure the harmonization of green financing policies and standards not only at the national but also at the global level.